Factors Associated with Stunting in The Work Area of Mangulewa Public Health Center, Golewa Barat Sub-District, Ngada District - Maria Clarita Faustina Dhiu; Intje Picauly; Honey Ivone Ndoen (Universitas Nusa Cendana, 2022)
The first five years of a child's life are crucial since children's growth and development occur at a rapid pace throughout this time. If there is an imbalance in consumption, the height will be affected. Stunting in children under the age of five is usually caused by long-term malnutrition. The number of stunting of five-year-old children at Mangulewa Public Health Center (PHC) in 2019 amounted to 178 cases. In 2020, there were 171 cases, including 123 short and 48 very short children. This study aims to determine the factors associated with the incidence of stunting in West Golewa District in 2020. This study is quantitative with a case-control design. The population was all under five children in the work area of Mangulewa PHC. The sample consisted of 104 children divided into 52 sampel for both case and control groups. Simple random sampling was used to select the sample. The results showed that the level of maternal education, history of exclusive breastfeeding, history of infectious diseases, and consumption patterns, namely the type, amount, and frequency of eating. were found to be associated with the incidence of stunting. There was no link between birth distance and the occurrence of stunting. Stunting must be immediately handled as it has long and short-term consequences such as psychological development issues, slow body growth, decreased achievement, and learning ability. All of these factors will have an impact on the future of children under the age of five.